The COVID-19 cohort ward Experience: All hands on deck (2020)
The coronavirus disease (COVID-19) pandemic poses a substantial challenge to global healthcare systems. We hope to share our institution’s experience of using open, non-negative pressure cohort wards to deliver safe care to COVID-19 patients, as well as experience with a multi-specialty team to run the cohort wards. Our institution is a 1000-bedded tertiary, public hospital with a mixture of single occupancy rooms, and open multi-bedded cubicles.